Pronominalization, agency and identity: the (in) visibilisation of agency in the narrative discourse of single mothers in Mexico City - García Agüero, Alba N. (Boletín de Filología, 2023)
From a critical-discursive perspective and using the narrative as a unit of analysis, in this article I show some linguistic strategies with which a socially discriminated group, such as Mexican single mothers, negotiates its identity, protects its face and resists dominant discourses. The strategies we focus on are the pronominalization of yo; the use of tú without a pronoun in a collective sense; and the use of the marked gender of the pronouns nosotras and una. Through different narrative extracts, elicited in semi-directed interviews with six single mothers, I illustrate the functions that these linguistic elements fulfill. The results show that pronominalization has an agentive function that is part of a face-work (Brown and Levinson 1987); the second person singular without a pronoun is a face-protecting strategy, while the use of marked gender has a differentiating function. This analysis shows that it is essential to consider the complete communicative situation in which the narratives arise in order to assign meaning to the use of such linguistic strategies.